2001
DOI: 10.1016/s1074-5521(01)00014-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of Celmer’s rules: role of the ketosynthase domain in epimerisation and demonstration that ketoreductase domains can have altered product specificity with unnatural substrates

Abstract: These results demonstrate that the epimerising activity associated with module 1 of the erythromycin PKS can be conferred on module 5 merely by transfer of the KS1 domain. Moreover, the normally precise stereochemical control observed in modular PKSs is lost when KR5 and KR6 are challenged by an unfamiliar substrate, which is much smaller than their natural substrates. This observation demonstrates that the stereochemistry of ketoreduction is not necessarily invariant for a given KR domain and underlines the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
45
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 36 publications
2
45
2
Order By: Relevance
“…For example, the reductive loop of DEBS module 5, which in its native context gives a (2R,3S) configuration in the alcohol product, was cloned into AvrII-HpaI sites (in S. erythraea JC2, pJCE5), and the fermentation of the resulting strain gave comparable yield and identical products to the control derived from DEBS module 2. This outcome makes a telling contrast to the results of previous in vivo work, [30] in which KS 5 was replaced by the DEBS loading module and KS 1 in DEBS 3. The products of that hybrid multienzyme included not only the normal products of DEBS3, but also an aberrant triketide lactone.…”
contrasting
confidence: 88%
See 3 more Smart Citations
“…For example, the reductive loop of DEBS module 5, which in its native context gives a (2R,3S) configuration in the alcohol product, was cloned into AvrII-HpaI sites (in S. erythraea JC2, pJCE5), and the fermentation of the resulting strain gave comparable yield and identical products to the control derived from DEBS module 2. This outcome makes a telling contrast to the results of previous in vivo work, [30] in which KS 5 was replaced by the DEBS loading module and KS 1 in DEBS 3. The products of that hybrid multienzyme included not only the normal products of DEBS3, but also an aberrant triketide lactone.…”
contrasting
confidence: 88%
“…[30] In the present case, bringing KR 5 into a chimaeric module with KS 2 did not lead to any loss of stereospecificity or stereoselectivity; this supports a model for catalysis [26,27,30] in which DEBS KS 2 differs from KS 1 in that it cannot catalyse the epimerisation of the (2R)-2-methyl-3-ketopentanoyl-ACP intermediate, or cannot do so fast enough to compete with ketoreduction. This experiment also shows that the ACP-tethered diketide is reduced with full fidelity by KR 5 , even though previous in vitro studies have shown that recombinant purified KR 5 reduces the (untethered) racemic substrate (2RS)-2-methyl-3-oxopentanoic acid N-acetylcysteamine thioester to give three stereoisomeric products.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Althoughi tw as initially proposed that the KS domains were also responsible for epimerization thus yieldingt he l-configuration observed in many polyketides, [13,14] it is now clear that lmethyl groups arise from the epimerase activity of certain KR domains, even when the KRs are inactive as ketoreductases. [15][16][17][18] This understanding has led to the classification of modular PKS KR domains into six types: [15] those catalyzing ketoreduction but not epimerization (A1 and B1), ketoreductiona nd epimerization (A2 and B2), epimerization but not reduction (C2), and fully inactive KRs (C1).…”
Section: Introductionmentioning
confidence: 99%